Effect of low-energy proton radiation on the degradation of silicon carbide Schottky diodes - Baba, Tamana; Hasbullah, Nurul Fadzlin; Javed, Yasir; Khan, Zafar Iqbal; Sulaiman, Nurul Nabiilah (Springer, 2025)
Silicon carbide (SiC) Schottky diodes are gaining traction for their potential in high-voltage, high-temperature, and radiation-resistant applications. While superior to traditional silicon (Si) diodes, their radiation hardness requires further exploration, particularly at lower energies. Although high-energy radiation undoubtedly degrades devices, understanding the impact of lower-energy radiation is crucial for real-world applications. This study employed 8 MeV proton radiation, considered relatively low energy in radiation physics, to investigate the response of SiC Schottky diodes. Interestingly, the irradiated devices displayed a slight decrease in reverse leakage current, indicating improved blocking ability. Encouragingly, both forward current and capacitance remained relatively unaffected, with a minor change in the ideality factor. Microscopy confirmed these findings by revealing no surface-level defects or leakage current hotspots, solidifying the exceptional resilience of SiC Schottky diodes to even lower-energy radiation.